The Islamic Religious Observance Scale; development, psychometric properties and associations with demographic factors in a Sudanese sample - Shennan, Ahmed M. El-Hassan (Tafakkur; Vol 4 No 1 (2002), 2002)
This study reports the development and a preliminary analysis of the psychometric properties of the Islamic Religious Observance Scale “IROS”. The IROS measures the concept of religiosity from an Islamic perspective. One hundred Sudanese Muslim adults completed the Islamic Religious Observance Scale. The IROS was found to have satisfactory test-retest reliability, good internal consistency and good construct validity. The author believes that the IROS might have utility for screening and research purposes, not only as an assessment and outcome measure but also for testing hypotheses about connections between religion and mental health in the Sudan and other Islamic countries.